Apakah Pengendalian Internal Penting? Menilai Perannya Dalam Mengamankan Integritas Pendapatan Pasien BPJS Di RSIA Permata Hati Mataram - Wati, Cinta; Lariska, Auliana; Prasetia, Ade; Fitriah, Nur (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the importance of internal control in securing the integrity of BPJS patient income at Permata Hati Mataram Mother and Child Hospital. The method used is a qualitative approach with a descriptive study type, through data collection techniques in the form of interviews, participant observation, and documentation. The results showed that internal control in the hospital had included separation of work functions, tiered verification, and fairly good internal coordination. However, there are still obstacles in technical aspects such as errors in the E-Claim system and document mismatches that cause pending or failed claims. This condition has an impact on delayed revenue and an increase in uncollectible receivables. Thus, internal control proves to play an important role in maintaining the financial integrity of hospitals that depend on revenue from BPJS Kesehatan.